Dislocations in solids. - Hirth, John Price, 1930-; Kubin, L. (North Holland, 2010)
New materials addressed for the first time include the chapters on minerals by Barber et al and the chapter on dislocations in colloidal crystals by Schall and Spaepen. Moriarty et al extend the first principles calculations of kink configurations in bcc metals to high pressures, including the use of flexible boundary conditions to model dilatational effects. Rabier et al clarify the issue of glide-shuffle slip systems in diamond cubic and related III-V compounds. Metadislocations, discussed by Feuerbacher and Heggen, represent a new type of defect in multicomponent metal compounds and alloys. Kink mechanisms for dislocation motion at high pressure in bcc metals Dislocation core structures identified in silicon at high stress Metadislocations, a new type of defect, identified and described Extension of dislocation concepts to complex minerals First observations of dislocations in colloidal crystals.